2018
DOI: 10.1093/neuros/nyy474
|View full text |Cite
|
Sign up to set email alerts
|

Is Preoperative Duration of Symptoms a Significant Predictor of Functional Outcomes in Patients Undergoing Surgery for the Treatment of Degenerative Cervical Myelopathy?

Abstract: BACKGROUND Preoperative duration of symptoms may significantly impact outcomes in patients treated surgically for degenerative cervical myelopathy (DCM). OBJECTIVE To (i) analyze whether duration of symptoms is associated with preoperative functional impairment, disability, and quality of life and (ii) determine the optimal timing for decompressive surgery. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…The Table 3 shows the analysis of changes in the outcome parameter mJOA pre and postoperatively. The patients were divided according to preoperatively mJOA score in three groups, mild (mJOA˃15), moderate (mJOA [12][13][14] and severe myelopathy (mJOA ˂12). The extent of improvement was statistically significant in all three category of patients according to mJOA score (p˂0,001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Table 3 shows the analysis of changes in the outcome parameter mJOA pre and postoperatively. The patients were divided according to preoperatively mJOA score in three groups, mild (mJOA˃15), moderate (mJOA [12][13][14] and severe myelopathy (mJOA ˂12). The extent of improvement was statistically significant in all three category of patients according to mJOA score (p˂0,001).…”
Section: Resultsmentioning
confidence: 99%
“…It seems well established that the surgical treatment of CSM is better than no treatment, although even this assumption continuous to be questioned. The results of some study indicate that the outcome of surgically treated CSM has not been better in comparison to the natural history or nonoperative therapy and notes that there are no clear guidelines for selection of patients who will benefit from surgery, while other study favored surgical management (6,12,13). The confounding variables are the often slow, variable natural history and the absence of randomized, controlled studies to allow evidence-based treatment choices (6,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study also revealed that hyperechogenicity in the dorsal part was more severe than that of the ventral spinal cord, while the RR of the JOA-S score was not as good as that of the JOA-M score. Previous studies that focused on the prevalence of pre- or post-operative symptoms of DCM also reported that sensory impairment was more common and more persistent [ 25 26 ]. For DCM, compression of the spinal cord is always from the ventral aspect, but the impairment based on IOUSI occurred more often and was more severe in the dorsal part.…”
Section: Discussionmentioning
confidence: 99%
“…Symptom duration was described as a negative outcome predictor in several studies [18,23,24]. Holly et al highlight the importance of symptom duration and age for the postoperative outcome of DCM patients [17].…”
Section: Discussionmentioning
confidence: 99%